ANALYSIS OF FACTORS AFFECTING THE INCOME OF TRADERS AT UJUNG GADING MARKET: ANALYSIS OF FACTORS AFFECTING THE INCOME OF TRADERS AT UJUNG GADING MARKET - Fajri al fajri; Yossi Eriawati; Novi Susanti (At Tasyri'i : Jurnal Program Studi Perbankan Syariah, 2023)
The researcher started this study after noticing that, as of late, the coronavirus outbreak and internet retailers (Ol-Shop), the income of vendors at Ujung Gading Market has been erratic. Because of this volatility, fewer buyers and more competition have resulted in lower sales for many dealers. Therefore, the researcher's goal is to find out if the capital, length of business operation, and trader education level variables have an impact on traders' income at Ujung Gading Market. With primary data gathered via surveys, this study used a quantitative methodology. 603 traders make up the study's population, and 216 respondents were chosen at random for the sample using the simple random sampling method. Multiple linear regression analysis approaches were used in SPSS version 25 to process the acquired data. The study's findings suggest that traders' income is influenced by the capital variable to some extent. The t-significance value of 0.000 < 5% in the SPSS report supports this. A t-significance value of 0.001 < 5% suggests that the Length of business operation variable also has a partial impact on traders' income. An SPSS output with a t-significance value of 0.003 < 5% indicates that the education variable also has a partial impact on traders' income. The findings also indicate that the revenue of traders at Ujung Gading Market is influenced simultaneously by capital, length of business operation, and education.The fact that the F-count value of 34.481 > the F-table value of 2.647 and the F-significance value of 0.000 < 5% support this. As a result, H0 is disproved and hypothesis Ha is approved. This clarifies why capital (X1), length of business operation (X2), and education (X3) all affect income concurrently and to a strength of 32.8%. Keywords : the income; traders; capital; Length of business operation; education